YouTube as a Medium for Preaching and Counseling:: Digital Opportunities and Challenges - Fahira Hidayah, Rifa; Nuzulia, Rahmadaniatul (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The advancement of digital technology has transformed Islamic preaching (dakwah) and counseling, with YouTube emerging as one of the most influential platforms. This study examines the effectiveness of YouTube in disseminating Islamic messages and the challenges of using it for online counseling. Employing a qualitative content analysis of selected channels, the research finds that YouTube effectively engages audiences through interactive features such as comments and live chats, while its flexibility allows users to access content anytime and anywhere. Creative and contextual approaches in dakwah content have enhanced religious understanding and attracted younger audiences. However, the use of YouTube for counseling faces limitations, including privacy risks, reduced non-verbal interaction, and the spread of unethical or misleading content. The study concludes that professionalism, digital literacy, and strong ethical standards are essential to maximize YouTube’s role as a safe and effective medium for dakwah and counseling.